Skolēnu radošā darbība tamborēšanas un adīšanas pamatu apguvē mājturībā un tehnoloģijās 4.klasē - Kozlovska, Inga (Latvijas Universitāte, 2012)
Ingas Kozlovskas diplomdarba „Skolēnu radošā darbība tamborēšanas un adīšanas pamatu apguvē mājturībā un tehnoloģijās 4. klasē” mērķis ir izpētīt radošās darbības veicināšanas iespējas tamborēšanas un adīšanas pamatu apguvē 4. klasē mājturībā un tehnoloģijās. Darba teorētiskajā daļā ir raksturots radošuma jēdziens, kurš cieši saistīts ar skolēna mērķtiecību un saistību ar viņa augšanu, attīstību, audzināšanu. Analizēts mācību saturs tamborēšanas un adīšanas apguvei 4. klasē mājturībā un tehnoloģijās. Praktiskajā daļā izveidots tematiskais plāns radošās darbības veicināšanai mājturībā un tehnoloģijās 4. klasē, kurš aprobēts, analizēti iegūtie rezultāti. Atspoguļoti skolēnu un skolotāju pētījuma rezultāti, kuri parāda informāciju par radošuma sekmējošajiem faktoriem mājturības un tehnoloģiju stundās. Atslēgas vārdi: mājturība un tehnoloģijas, radošā darbība, tamborēšana un adīšana.

The aim of Inga Kozlovska’s diploma paper “Pupils’ Creative Activity in the Acquisition of Basic Crocheting and Knitting in Home Economics and Technology Lessons in Grade 4” is to explore the ways to encourage creative activity in acquiring crocheting and knitting basics in grade 4 at Home Economics and Technology lesson. In the theoretical part of the Paper the definition of creativity is described. It is closely connected with pupil’s determination and connection with his / her growth, development, and upbringing. The analysis of curriculum for Crocheting and Knitting acquiring in grade 4 Home Economics and Technology lessons has been carried out. In the practical part the teaching plan for encouraging creative activity in grade 4 was developed and approbated, and the gained results analyzed. The results of the students and teachers research that show information about creativity encouraging factors at Home Economics and Technology lessons are represented. Key words: creative activity, crocheting and knitting. Home Economics and Technology,
Pupils’ creative activity in the acquisition of basic crocheting and knitting in home economics and technology lessons in Grade 4
Keywords: Pedagoģija